Prehabilitation for adults diagnosed with cancer: A systematic review of long‐term physical function, nutrition and patient‐reported outcomes. (11th March 2019) - Faithfull, Sara; Turner, Lauren; Poole, Karen; Joy, Mark; Manders, Ralph; Weprin, Jennifer; Winters‐Stone, Kerri; Saxton, John
Abstract: Objective: Prehabilitation is increasingly being used to mitigate treatment‐related complications and enhance recovery. An individual's state of health at diagnosis, including obesity, physical fitness and comorbidities, are influencing factors for the occurrence of adverse effects. This review explores whether prehabilitation works in improving health outcomes at or beyond the initial 30 days post‐treatment and considers the utility of prehabilitation before cancer treatment. Methods: A database search was conducted for articles published with prehabilitation as a pre‐cancer treatment intervention between 2009 and 2017. Studies with no 30 days post‐treatment data were excluded. Outcomes post‐prehabilitation were extracted for physical function, nutrition and patient‐reported outcomes. Results: Sixteen randomised controlled trials with a combined 2017 participants and six observational studies with 289 participants were included. Prehabilitation interventions provided multi‐modality components including exercise, nutrition and psychoeducational aspects. Prehabilitation improved gait, cardiopulmonary function, urinary continence, lung function and mood 30 days post‐treatment but was not consistent across studies. Conclusion: When combined with rehabilitation, greater benefits were seen in 30‐day gait and physical functioning compared to prehabilitation alone. Large‐scale randomised studies are required to translate what is already known from feasibility studies to improve overall health and increase long‐term cancer patient outcomes.